The CounterText Interview: Mark McGurl. - McGurl, Mark; Herbrechter, Stefan (CounterText, 2022)
If one sets the bar as high as George Steiner does, we're of course unlikely to find a posthuman tragedy, or put differently, posthumanism is unlikely to (want to) produce a tragedy - two very different things. Whether one is talking about posthuman tragedy, or posthuman comedy - or, for that matter, posthuman lyric, or posthuman epic, or drama, and so on - what is at issue is the ontology and social function of literature across time. So the question that motivated me in looking into the relationship between posthumanism and the posthuman (and they are not the same) and tragedy and the tragic is very general, maybe even anthropological, or rather postanthropological, since posthumanism as I understand it is a theoretical paradigm that takes the idea of postanthropocentrism seriously, even literally. Maybe, if "we have never been human", if "we have become posthuman", or, if "we have always already been posthuman"... if the "best" or "worst" lies either behind or before us, the genre of tragedy might actually play a foundational role in posthumanism.